2018
DOI: 10.1186/s12866-018-1338-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Mannheimia haemolytica isolates associated with pneumonic cases of sheep in selected areas of Central Ethiopia

Abstract: BackgroundMannheimia haemolytica has been recognized as the principal cause of pneumonic pasteurellosis in sheep and goats. It is one of the important diseases of small ruminants in Ethiopia. While annual vaccination using a monovalent vaccine (inactivated Pasteurella multocida biotype A) is common, respiratory diseases are still reported in various parts of Ethiopia. This suggests the need for further investigation into the species and strains responsible for the disease, which is vital information for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
5
29
1
Order By: Relevance
“…Phylogenetic analyses comparing partial Rpt2 gene sequences of the Moroccan field isolate with reference and variant strain sequences revealed that the Moroccan isolate was homologous with the American genotype, especially Mha (USDA/ ARS/USMARC/184) isolated in the USA in 2013. This homology in genotype distribution among the Mha isolates observed agrees with the findings of Legesse et al [15], which revealed the existence of three genotypes of Mha circulating in the study areas consistent with the site of isolation. The growth kinetics of the Mha isolate in broth media showed a latency phase of 5 h, followed by an exponential phase of 3.5 h and a stationary phase of 1.5 h. The comparative growth kinetics between the local isolate and the reference strain of bovine origin (ATCC) revealed a higher bacterial concentration with the isolate than with the referred ATCC strain with 1 log difference.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Phylogenetic analyses comparing partial Rpt2 gene sequences of the Moroccan field isolate with reference and variant strain sequences revealed that the Moroccan isolate was homologous with the American genotype, especially Mha (USDA/ ARS/USMARC/184) isolated in the USA in 2013. This homology in genotype distribution among the Mha isolates observed agrees with the findings of Legesse et al [15], which revealed the existence of three genotypes of Mha circulating in the study areas consistent with the site of isolation. The growth kinetics of the Mha isolate in broth media showed a latency phase of 5 h, followed by an exponential phase of 3.5 h and a stationary phase of 1.5 h. The comparative growth kinetics between the local isolate and the reference strain of bovine origin (ATCC) revealed a higher bacterial concentration with the isolate than with the referred ATCC strain with 1 log difference.…”
Section: Discussionsupporting
confidence: 92%
“…Amplification of the Rpt2 gene sequence by PCR was performed using the Rpt2 forward (5′-GTT TGT AAG ATA TCC CAT TT-3′) and reverse (5′-CGT TTT CCA CTT GCG TGA-3′) primers [15]. PCR was performed using the Applied Biosystems kit protocol, in a 20-μL reaction mixture containing 2 μL buffer (10×), 2.5 μL MgCl 2 ( 25 mmol/l), 2.5 μL dNTP (10 mmol/l), 0.75 μL of each primer (10 μmol/l), 10.2 μL of sterilized water, 0.5 μL of RNase inhibitor (20 U/μL), 0.3 μL RT (50 U/μL), and 0.5 μL of Gold Taq polymerase (5 U/μL).…”
Section: Pcr For Rpt2 Gene Detection and Dna Sequencingmentioning
confidence: 99%
“…Respiratory rate, rectal temperature, nasal discharge, cough, dyspnea, percussion and altered sounds in pulmonary auscultation were increased in pneumonic sheep (P<0.05). These findings confirm the importance of the observed clinical signs of sheep to determine the respiratory health during physical examination (Viana et al 2007, Legesse et al 2018.…”
Section: Discussionsupporting
confidence: 83%
“…P. haemolytica biotype A was later allocated to a new genus Mannheimia and renamed as M. haemolytica , while the four T serotypes were named Bibersteinia trehalosi . Later, serotype A:11 was classified into a new taxon as M. glucosida , due to its different biochemical profile, leaving 12 serotypes of M. haemolytica [ 9 ].…”
Section: Introductionmentioning
confidence: 99%